Meningkatkan Kemampuan Bernalar Siswa SD pada Pembelajaran IPA dengan Pendekatan Pembelajaran Saintifik dan Kegiatan Storytelling - Septina Severina Lumbantobing; St Fatimah Azzahra (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2020)
The purpose of this study is to get a picture of the increase in reasoning ability of students who get science learning with a scientific approach combined with storytelling activities. This research was conducted at Elementary School 07 Jakarta semester 2019/2020. This type of research is a quasi experiment with the research design used one group pretest posttest group design. The sample in this study amounted to 50 students. The instrument used was a test of reasoning ability for subject matter always saving energy in the form of an essay test of 15 questions. The aspects of reasoning ability studied consisted of aspects of identifying, explaining and analyzing. The results showed the students' reasoning ability increased by 0.57 in the medium category. For the 3 aspects of reasoning ability studied, there was an increase in the identifying aspect by 46%, the explaining aspect by 94% and the analysis aspect by 88%. Keywords : reasoning ability, scientific approach, storytelling